Risk of Serious Infections in Patients Treated With Biologic or Targeted‐synthetic Disease Modifying Antirheumatic Drugs in Qatar - Sreethish Sasi; Hamad Abdel Hadi; Masautso Chaponda; Reem El Ajez; Mohamed Ataelmanan; Sief Khasawneh; Hind Saqallah; Maisa Ali; Nabeel Abdulla; Javed Iqbal; Ali S. Omrani; Muna Al Maslamani; et al. (Immunity, Inflammation and Disease)
ABSTRACT Background Biologic and targeted‐synthetic disease‐modifying antirheumatic drugs (b/tsDMARDs), are pivotal in the management of autoimmune‐inflammatory disorders, acting by suppressing pathological immune activation. Because of associated immune dysfunction, opportunistic or serious infections (SIs), and latent disease reactivation is frequently reported. This study aimed to investigate the epidemiology, risk factors, and outcomes of SIs in patients treated with b/tsDMARDs in Qatar. Methods A retrospective cohort study was conducted at Hamad Medical Corporation, including all the patients treated with one of 10 b/tsDMARDs, between January 2017 and July 2021. Besides descriptive statistics, the Chi‐square test and Kaplan–Meyer survival analysis were used for statistical analysis. Results Out of 1092 patients, 86 (7.9%) had SIs, with an incidence rate of 39.4 per 1000 patient years. Mean duration of onset was 10.8 months post‐initiation of therapy. Younger age groups (18–52 years) were predominantly affected. A significant association was observed between the primary diagnosis (rheumatological followed by gastrointestinal, neurological, and dermatological disorders) and the occurrence of SIs (χ² = 9.512, p < 0.050). Adalimumab and infliximab had a higher risk of SIs compared to other b/tsDMARDs. There was no significant difference between TNF‐inhibitors and others. Ocrelizumab was significantly associated with incidence of COVID‐19 SIs (χ² = 16.84, p = 0.0000408), and etanercept with Staphylococcus aureus SIs (χ² = 17.51, p = 0.0000285). Predominant infection sites were skin–soft tissue and respiratory tract. Most of the SIs were secondary to either bacteria (43%) or viruses (17.4%). The mean duration of hospitalization was 9 days, and 7% of patients required critical care, with no recorded 90‐day mortality. Conclusions Patients with inflammatory conditions managed with b/tsDMARDs are at significant risk of SIs, which necessitate appropriate patient selection weighing benefits and risks, as well as careful long‐term management that include patient education and relevant preventive therapy.